MULTIPLE NUCLEAR RECEPTORS MAY REGULATE HEPATITIS B VIRUS BIOSYNTHESIS DURING DEVELOPMENT - Reese, Vanessa (2009)
Hepatitis B virus (HBV) replicates by the reverse transcription of the viral 3.5kb pregenomic RNA. Therefore the level of expression of this transcript in the liver is a primary determinant of HBV biosynthesis. In vivo neonatal transcription of the HBV 3.5kb pregenomic RNA is developmental regulated by hepatocyte nuclear factor 4α (HNF4α). In addition, viral biosynthesis in non-hepatoma cells can be supported directly by this nuclear receptor. However HBV transcription and replication can be supported by additional nuclear receptors including the retinoid X receptor α/peroxisome proliferator-activated receptor α (RXRα/PPARα), retinoid X receptor α/farnesoid X receptor α (RXRα/FXRα), liver receptor homolog 1 (LRH1) and estrogen-related receptors (ERR) in non-hepatoma cells. Therefore during neonatal liver development, HNF4α may progressively activate viral transcription and replication by binding directly to the proximal HNF4α recognition sequence within the nucleocapsid promoter. Alternatively, HNF4α may support viral biosynthesis in vivo indirectly by activating a network of liver-enriched nuclear receptors that, in combination, direct HBV 3.5kb pregenomic RNA transcription and replication.